Ferritin–albumin ratio as a prognostic marker in children with sepsis admitted to a tertiary care centre - Jain, Sajal; Gupta, Ratan (International Journal of Contemporary Pediatrics, 2026)
Pediatric sepsis remains a major cause of morbidity and mortality worldwide, particularly in low- and middle-income countries. Early risk stratification is essential for timely intervention; however, existing clinical scores and biomarkers may be limited by complexity or delayed availability. Serum ferritin, a positive acute-phase reactant, reflects systemic inflammation, while albumin, a negative acute-phase reactant, reflects disease severity and physiological reserve. The ferritin–albumin ratio (FAR) integrates these opposing responses and may serve as a simple prognostic marker in pediatric sepsis. This prospective observational study included 114 children aged 1 month to 12 years admitted with sepsis at a tertiary care hospital. Clinical features, laboratory parameters, and outcomes were recorded. Serum ferritin and albumin levels measured within the first 24 hours of admission were used to calculate the ferritin–albumin ratio. Outcomes assessed included disease severity, pediatric intensive care unit (PICU) admission, requirement of mechanical ventilation, shock, and mortality. Receiver operating characteristic (ROC) curve analysis was performed to evaluate the prognostic performance of FAR. Children with higher FAR values had significantly higher pSOFA scores and were more likely to require PICU admission, mechanical ventilation, and develop shock. Median FAR was significantly higher among non-survivors compared to survivors. FAR demonstrated excellent discrimination for mortality on ROC analysis, with an area under the curve of 1.00 and high sensitivity and specificity at optimal cut-off values. FAR is a simple, inexpensive, and readily available prognostic marker that can reliably aid early risk stratification and outcome prediction in children with sepsis.